Application of Multidimensional Wave Digital Filters to Boundary Value Problems - Krauss, Herbert; Rabenstein, Rudolf (IEEE Signal Processing Letters, 1995)
The application of multidimensional wave digital filter principles to the numerical solution of partial differential equations has been introduced in various recent publications. However, the examples presented so far did not explicitly consider boundary conditions. This letter shows how to incorporate boundary values into a multidimensional wave digital filter. A lossy transmission line of finite extent with given terminations is chosen as an example. © 1995 IEEE